The Effect of Method of Collection and Number of Sequential Ejaculates on Semen Characteristics of Beef Bulls - A. R. Hartman; M. L. Butler; S. K. Tucker; N. M. Goodenow; J. M. Bormann; D. M. Grieger (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective of this study was to determine the effect of collection method and number of sequential ejaculates on beef bull ejaculate characteristics. Study Description:Semen collection data from 2008 to 2018 was obtained from the Kansas Artificial Breeding Services Unit and consisted of 11,642 ejaculates from 906 bulls. Bulls were collected twice weekly on Mondays and Thursdays with an artificial vagina. Bulls not receptive to the artificial vagina were subject to electro-ejaculation. A single technician was responsible for all pre-freeze and post-thaw semen analysis. Ejaculates were required to meet quality standards. Results:Progressive motility before freezing was greater (P<0.0001) for bulls collected with electro-ejaculate compared to artificial vagina. Ejaculate volume for electro-ejaculate collections was greater (P<0.0001) than those collected with artificial vagina. Percent spermatozoa with secondary abnormalities was greater (P<0.05) for bulls collected with electro-ejaculate compared to artificial vagina. Concentration of spermatozoa/mL was less (P<0.0001) for bulls collected with an electro-ejaculate (514 × 106) compared to artificial vagina (617 × 106). Total number of straws frozen/ejaculate was less (P<0.001) for bulls collected with electro ejaculate (94) compared to artificial vagina (108). The number of ejaculates collected/day was significant for the percent of spermatozoa with secondary abnormalities (P<0.001). As ejaculate number/day increased, the concentration of spermatozoa decreased (713, 580, 535, and 434 × 106/mL, respectively;P<0.0001) and the number of straws frozen/ejaculate decreased (123, 107, 93, and 82, respectively;P<0.0001). The Bottom Line:Producers and collection facilities should work together to balance collection method and number of ejaculates collected/day to maximize production while maintaining semen quality.
Keywords: artificial vagina; electro-ejaculation; semen